An Emerging Innovation Ecosystem for New Space—Kvarken Space Center in Finland - Punnala, Mikko; Ratilainen, Jari (Palgrave Macmillan, 2024)
This chapter explores the burgeoning innovation ecosystem in the New Space sector, with a specific focus on the Kvarken Space Center in Finland. It delves into the center’s role in catalyzing the regional space economy, highlighting key development opportunities and challenges identified from the industry needs. The overarching aim of these scholarly endeavors is to establish a sustainable innovation ecosystem tailored to regional New Space activities, thereby fostering long-term economic development centered on space-based business and innovation. The study employs qualitative methodologies, including interviews and data analysis, to capture the dynamic interactions within the ecosystem. The chapter also examines the unique contributions of the Kvarken Space Center and the pivotal role of academia as the key driver in fostering an innovative environment. Findings underscore the necessity of collaboration among different ecosystem players and the potential impact of such synergy on the wider New Space Economy. The chapter concludes with policy recommendations aimed at nurturing and sustaining innovation within this rapidly evolving sector. This study not only sheds light on the Kvarken Space Center's influence but also provides insights relevant to similar New Space Ecosystems globally.
Keywords: New Space Economy; Innovation ecosystem; Kvarken Space Center; Satellite remote sensing; Space data utilization